An Android-Based Information System for Enhancing Rural Transportation Services in Banjarnegara, Indonesia - Abdan Zaki Alifian; Ridho Muktiadi; Tito Pinandita; Ermadi Satriya Wijaya (Journal of ICT, Design, Engineering and Technological Science, 2024)
Transportation is the movement of people or goods from one place to another using a tool driven by humans or machines. The large number of people in Banjarnegara Regency makes the need for rural transportation in Banjarnegara regency very important, especially for those who do not have private vehicles to travel from one place to another. Mobile technology is developing very fast, both in terms of hardware and software. Mobile-bile technology can now be used in various